Youth experiences with and perspectives on long covid - Sarosh Irani; Claire Chang; Leigh Morrison; Marika Waselewski; Tammy Chang (BMC, 2023)
Abstract Background Research on the long-term effects of COVID-19 infection is ongoing, and the psychological and physical impacts of Long Covid on youth is poorly understood. To assess these impacts, we surveyed youth regarding their experiences with, and perspectives on, the long-term effects of COVID-19. Methods We conducted a nationwide text message survey of youth ages 14-24 years in the United States. The survey asked four open ended questions regarding their experiences and perceptions regarding the long-term effects of COVID-19. Qualitative data was analyzed independently by three investigators using thematic analysis. Prevalence of codes were summarized using descriptive statistics. Results Among 1150 participants, 991 responded to at least one survey question (response rate 86.1%). The vast majority of our sample had COVID-19 or knew someone who did (75%), and approximately one third (32%) of youth indicated that they knew someone who had experienced symptoms consistent with Long Covid. Many youth (50%) reported worry and concern about Long Covid even if they, or someone they knew, did not have Long Covid. Among youth who were not concerned about Long Covid, the most commonly reported reasons were having received the vaccine (29%) and not having a prior COVID-19 infection (24%). Conclusions Our findings suggest that among younger populations, there is significant concern regarding the long-term effects of COVID-19. Vaccination campaigns and youth-centered public health communication about Long Covid may not only reduce COVID-19 transmission, but also alleviate worries and concerns about Long Covid among youth.